Defense Against Criminal Theft Perpetrators Based on Islamic Law - Muhammad Abdi Manullang; Pagar Pagar; Ramadhan Syahmedi Siregar (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to describe the legality of the defense of suspected perpetrators of criminal acts of theft carried out by LBH SIKAP based on Islamic law. This study is a field research (empirical study), using the results of observations and interviews with LBH SIKAP Advocates of Dairi Regency and the people of Dairi Regency as primary sources. Secondary sources include laws and regulations, including the Criminal Code (KUHP) and Law Number 16 of 2011 concerning Legal Aid. The results of the study: The practice of efforts to defend suspects in the crime of theft carried out by LBH SIKAP by way of direct assistance when the perpetrators are still at the investigation level; LBH SIKAP will provide assistance until the file is brought to the prosecutor's office so that the prosecution is carried out immediately, to assist the person who has the status of a defendant before the Panel of Judges of the Sidikalang District Court. The defense carried out by LBH SIKAP was carried out based on a request from the perpetrator or the perpetrator's family after an arrest by the police. LBH SIKAP advocates studied the files; then, the family approached the perpetrators to provide protection and assistance. The defense of suspected perpetrators of the crime of theft carried out by LBH SIKAP based on Islamic law is not prohibited. In general, the defense carried out by LBH SIKAP is part of professionalism and has been guaranteed by law. Penelitian ini bertujuan untuk mendeskripsikan legalitas pembelaan tersangka pelaku tindak pidana pencurian yang dilakukan oleh LBH SIKAP berdasarkan hukum Islam. Penelitian ini merupakan penelitian lapangan (studi empiris), dengan menggunakan hasil observasi dan wawancara sebagai teknik pengumpulan data. Peneliti menjadikan masyarakat dan Advokat LBH SIKAP Kabupaten Dairi sebagai sumber primer. Sumber sekunder meliputi peraturan perundang-undangan, antara lain Kitab Undang-Undang Hukum Pidana (KUHP) dan Undang-Undang Nomor 16 Tahun 2011 tentang Bantuan Hukum. Hasil penelitian: Praktek upaya pembelaan tersangka tindak pidana pencurian yang dilakukan oleh LBH SIKAP dengan cara pendampingan langsung pada saat pelaku masih dalam tahap penyidikan; LBH SIKAP akan memberikan pendampingan hingga berkas tersebut dibawa ke kejaksaan agar segera dilakukan penuntutan, mendampingi pihak yang berstatus sebagai terdakwa di hadapan Majelis Hakim Pengadilan Negeri Sidikalang. Pembelaan yang dilakukan oleh LBH SIKAP dilakukan atas permintaan dari pelaku atau keluarga pelaku setelah dilakukan penangkapan oleh pihak kepolisian. Para advokat LBH SIKAP mempelajari berkas tersebut; Kemudian, pihak keluarga melakukan pendekatan kepada pelaku untuk memberikan perlindungan dan pendampingan. Pembelaan terhadap tersangka pelaku tindak pidana pencurian yang dilakukan oleh LBH SIKAP berdasarkan hukum Islam tidak dilarang. Secara umum, pembelaan yang dilakukan oleh LBH SIKAP merupakan bagian dari profesionalitas dan telah dijamin oleh undang-undang.